Inter-laboratory calibration of estimated oil equivalent (EOE) concentrations of a water accommodated fraction (WAF) of oil and a chemically enhanced WAF (CEWAF). Issue 1 (January 2019) - Bera, Gopal; Gold-Bouchot, Gerardo; Passow, Uta; Wade, Terry L.; Shi, Dawei; Morales-McDevitt, Maya; Ramirez-Miss, Noemi; Knap, Anthony H.; Quigg, Antonietta
Abstract: Chemical characterization of the presence of oil in environmental samples are performed using methods of varying complexity. Extraction of samples with an organic solvent and analysis by fluorescence spectrometry has been shown to be a rapid and effective screening technique for petroleum in the environment. During experiments, rapid analysis of oil by fluorescence provides the opportunity for researchers to modify the experimental conditions in real time. Estimated Oil Equivalents (EOE) relies on the fluorescence measurement of the aromatic compounds to estimate the oil concentration. The present intercalibration study was designed to investigate whether different fluorometer instruments can reliably measure EOE and whether the results are intercomparable. Additionally, the need for extraction of oil compounds into an organic solvent was investigated. Three different fluorometers were used in three different laboratories: a Horiba Aqualog, a Turner Trilogy and a Shimadzu Spectrofluorophotometer RF-1501. Results from these different instruments showed excellent agreement for EOE determinations. A very high correlation was found between the EOE results obtained with Aqualog Horiba and Turner Trilogy (r 2 = 0.9999), with no significant differences between the mean EOE results (t-test, p = 0.30), and the Aqualog Horiba and Shimadzu (r 2 = 0.995) fluorometers, with no statistically difference between the EOE results obtained by the two instruments (p = 0.40).